The alternative approach to the preparation of complex calcium phosphates and their characterization - Livitska, Ok.; Strutynska, N.; Livitska, Ol.; Slobodyanik, N. (Functional Materials, 2017)
In this paper a new approach to the preparation of complex calcium-containing phosphates using molten chlorides and nitrates of alkaline metals as fluxes was described. The main advantages of used technique for synthesis of double phosphates comparing with traditional methods (solid state reactions or crystallization of a high temperature self-flux) were discussed. It was found that the phase composition of obtained crystalline products depends on type of salt melts, nature of alkaline metals and type of initial components. Formation conditions for compounds MICaPO₄, MI₂CaP₂O₇ (MI - Na, K), Ca₂P₂O₇, Ca₂PO₄Cl and Ca₁₀(PO₄)₆Cl₂ were established. The synthesized phosphates were characterized using powder X-ray diffraction, Fourier transform infrared spectroscopy and optical microscopy.